Islamic Entrepreneurship : Case Study On PMW (Student Entrepreneurship Program) - W. Mahri, A. Jajang; Juliana, Juliana; Maulana, Riko Riza; Nurhayati, B. Lena; Faiz, Ihda Raifin (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
The purpose of this study was to further examine the character of Islamic Entrepreneurship among young entrepreneurs of UPI students. The research method used was descriptive quantitative analysis with a sample of 58 student respondents who passed the 2017-2018 UPI PMW. Data analysis techniques used in this study were descriptive statistical analysis using Microsoft Excel and SPSS. The results of this study indicate that the overall level of application of the characteristics of Islamic Entrepreneurship for students who passed the 2017-2018 UPI PMW was very good. It means that PMW 2017-2018 overall of UPI students has been aware of the importance, understand and apply the character of Islamic entrepreneurship very well. The novelty of this study is to target Muslim students to qualify for the 2017-2018 PMW at UPI to be able to express their attitude towards Islamic Entrepreneurship and by updating the Qona'ah dimension that did not exist in the previous studies which made the high Characteristics of Islamic Entrepreneurship very influential for Muslim development preneur in Indonesia. Besides, PMW overall for stakeholders to add Islamic nuance for students passing PMW to enhance their Islamic character.